171 Sex-Sorted Sperm Used for Fixed-Time Artificial Insemination and in Vitro Fertilization in Wood Bison. (21st September 2022) - Zwiefelhofer, Eric M; Adams, Gregg P; Zwiefelhofer, Miranda L; Mackie, Paula; Mastromonaco, Gabriela F
Abstract: Wood bison (Bison bison athabascae) are a threatened species native to Canada. In a conservation setting such as zoos, females are preferred over males and sex-sorted sperm may help skew the proportion of females born. The objective of this study was to determine the efficacy of sex-sorted sperm in fixed-time artificial insemination (FTAI, Experiment 1) and in vitro fertilization (IVF, Experiment 2). In Experiment 1, females in bison herds at the University of Saskatchewan and Toronto Zoo were synchronized with 3.3 mg estradiol-17ß + 50 mg progesterone and given a progesterone-releasing intravaginal device for 8 days. At device removal, bison were given 500 µg of cloprostenol, and 72 h later were given 2500 IU human chorionic gonadotropin (hCG) and inseminated with either sex-sorted or conventional sperm. A second insemination occurred 24 h after hCG. Pregnancy diagnosis and fetal sexing was done by transrectal ultrasonography at 30- and 70-days post-AI, respectively. In Experiment 2, cumulus oocyte complexes collected transvaginally from live bison were fertilized in vitro with either sex-sorted or conventional sperm. Cleavage and embryo rates were determined at 3- and 7-days post fertilization, respectively. Proportional data were compared by chi-square. In Experiment 1, there was no effect of herd (P=0.17) or sperm (P=0.68) on pregnancy per AI (P/AI) at 30 days (total=25/51 [49%]). The proportion of female calves was greater in the sex-sorted than conventional group (9/10 [90%] vs 3/11 [27%]; P< 0.01). In Experiment 2, the cleavage (122/222 [55%] vs 62/94 [66%];P=0.07) and embryo rate (18/222 [8%] vs 14/94 [15%]; P=0.07) tended to be lower in the sex-sorted than the conventional group. In summary, sex-sorted sperm increased the proportion of female bison calves born following FTAI. Future efforts will include improving embryo production rates following IVF with sex-sorted sperm. Funding provided by Toronto Zoo, Mitacs, and STGenetics.